2016
DOI: 10.2174/0929867323666160607120124
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Microglial Signaling Pathways: New Insights in the Modulation of Neuropathic Pain

Abstract: The microglia, once thought only to be supporting cells of the central nervous system (CNS), are now recognized to play essential roles in many pathologies. Many studies within the last decades indicated that the neuro-immune interaction underlies the generation and maintenance of neuropathic pain. Through a large number of receptors and signaling pathways, the microglial cells communicate with neurons, astrocytes and other cells, including those of the immune system. A disturbance or loss of CNS homeostasis c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
99
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(106 citation statements)
references
References 208 publications
(282 reference statements)
6
99
1
Order By: Relevance
“…There are many reports showing the morphological changes of activated microglia/macrophages after nerve injury in immunofluorescence studies . We observed, using Western blot analysis, a strong increase in the number of IBA‐1‐positive cells on the 7th day post‐CCI in the spinal cord and the DRG, which is in agreement with other data . Many of these works emphasize that the strong uncontrolled activation of microglia/macrophages is the cause of the development of neuropathic pain.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…There are many reports showing the morphological changes of activated microglia/macrophages after nerve injury in immunofluorescence studies . We observed, using Western blot analysis, a strong increase in the number of IBA‐1‐positive cells on the 7th day post‐CCI in the spinal cord and the DRG, which is in agreement with other data . Many of these works emphasize that the strong uncontrolled activation of microglia/macrophages is the cause of the development of neuropathic pain.…”
Section: Discussionsupporting
confidence: 91%
“…interleukin‐1 β (IL‐1 β ), IL‐18, IL‐6 and nitric oxide synthase 2 (NOS2)] and antinociceptive factors [e.g. IL‐1 receptor antagonist (IL‐1RA), IL‐18 binding protein (IL‐18BP) and IL‐10] contributes to the development of neuropathic pain . Moreover, research on chemokines has suggested that their systems (ligands/receptors) are involved in pathological nociceptive processes .…”
Section: Introductionmentioning
confidence: 99%
“…42 It is well known that ERK 43,44 and PI3K-Akt 27,45 activation are required for the initiation and maintenance of neuropathic pain. Using a PI model, Shi et al.…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB is a key transcription factor that has been shown to regulate the expression of pro-inflammatory factors involved in activated microglia [30]. A growing body of evidence suggests that inhibition of NF-κB can directly or indirectly promote neuroprotective M2 polarization of the microglia [31,32].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…The NF-κB family includes five members (p50, p52, p65, c-Rel, and Rel-B). In the nervous system, the phosphorylation of p65 helps stabilized NF-κB complex in the nucleus for gene expression and thereby is widely used as an indicator of NF-κB activation [30]. In addition, previous studies have reported that p65 phosphorylation induced microglia polarization [35,36].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%